Caregiving in the shadows: National analysis of health outcomes and intensity and duration of care among those who care for people with mental illness and for people with developmental disabilities. Issue 1 (January 2020) - Barnhart, Wesley R.; Ellsworth, David W.; Robinson, Ann C.; Myers, John V.; Andridge, Rebecca R.; Havercamp, Susan M.
Abstract: Background: The health impacts of caring for people with mental illness (MI) and developmental disabilities (DD) are not well understood. Objective: The present study explored whether health outcomes differed between MI and DD caregivers, and if intensity and duration of care moderated health outcomes. Methods: Nationally representative 2016 Behavioral Risk Factor Surveillance System survey data were used to explore how caring for people with MI ( n = 1071) and DD ( n = 888) impacted general health status and physical and mental health days, and whether intensity and duration of care moderated health outcomes. Logistic regression models and cumulative logistic regression models were used to model health outcomes. Results: Caregivers had worse health (p = 0.0001) and more poor physical (p < 0.0001) and mental health days (p < 0.0001) than non-caregivers. Relative to DD caregivers, MI caregivers had worse health status (p = 0.02) and more poor physical (p = 0.02) and mental (p = 0.003) health days. As intensity of care increased, MI caregivers had more poor physical health days (p = 0.04) than DD caregivers and as duration of care increased, MI caregivers had worse health status (p = 0.03) than DD caregivers. Conclusions: Although the care provided to adults with DD was more intense and for a longer duration, MI caregivers had poorer health outcomes and were more impacted by intensity and duration of care. Implications for supporting MI and DD caregivers are discussed.